Predictors of mortality among neonates hospitalized with neonatal sepsis: a case control study from southern Ethiopia - Tadele Bekele; Hailu Merga; Tamiru Tesfaye; Henok Asefa (BMC, 2022)
Abstract Background Neonatal sepsis, which resulted from bacterial, viral, and fungal invasions of the bloodstream, is the major cause of neonatal mortality and neurodevelopmental impairment among neonates. It is responsible for more than one-third of neonatal deaths in Ethiopia. Frequently neonates referred to health facilities are at high risk of death. Hence, assessing and preventing the predictors of mortality in neonatal sepsis helps to reduce the burden of neonatal mortality. Objectives To determine predictors of mortality among neonates admitted with sepsis at Durame general hospital, southern Ethiopia, 2020. Methods Institution-based unmatched case-control study was carried out from March 8 to 30, 2020, among 219 neonates in Durame general hospital in southern Ethiopia. Neonates admitted with sepsis and died were considered as cases and neonates admitted with sepsis and survived (discharged alive) as controls. Cases were selected by taking the deaths of neonates consecutively among those neonates admitted with the diagnosis of neonatal sepsis. The next immediate three corresponding controls were selected by lottery method from the Neonatal Intensive Care Unit (NICU) case registration book. Data was collected by using structured pretested checklists from neonates' records and then entered into Epi data version 3.1 and exported to SPSS version 20. Logistic regression was used to identify the predictors of mortality. Statistical significance was declared at P < 0.05. Results A total of 55 cases and 164 controls were included in this study. More than three quarters (81.8%) of cases had early onset sepsis. The multivariable logistic regression analysis showed that predictors of mortality in this study were; poor feeding [AOR = 4.15; 95% CI (1.64, 10.49)], respiratory distress [AOR = 2.72; 95% CI (1.31, 5.61)], estimated gestational age less than 37 weeks [AOR = 4.64; 95% CI (2.17, 9.91)], and convulsion [AOR = 3.13; 95% CI (1.12, 8.76)]. Conclusion This study showed that prematurity, convulsion, poor feeding, and respiratory distress were the predictors of sepsis-related neonatal mortality. It is important to pay attention to septicemic babies with any of the identified predictors to reduce sepsis-related mortality.